Dollarization in Jordan - Hijazeen, Issa; Al-Assaf, Ali (International Journal of Economics and Financial Issues, 2018)
The study has investigated the main determinants of dollarization on the assets side and the liability side and financial dollarization using different measures. Following (Mogardini & Mueller, 1999), the econometric results indicated that interest rate differentials have little effect on currency substitution and deposit dollarization measures. Also, they implied that the REER movements do not contribute in the portfolio choice determination for depositors. However, the effect of international reserves was found to be significant and adversely related with dollarization. As for asset, the results illustrated that the effects of monetary policy decisions on extended foreign currency credit are significant only in the short run. The REER movements have a positive effect in the short run. The effect of reserves on asset dollarization was significant and positive only in the short run. As for financial dollarization, interest rate differentials had no significant impact indicating that portfolio allocation choices are determined by the volatility of inflation and the REER movements, which could be verified by the positive effect of the REER, whereas reserves had a significant negative impact on financial dollarization in the short and long run. The ratchet effect coefficient has a positive sign in all four models and its coefficients were significant in the short run and long run indicating the persistence of dollarization phenomenon in Jordan. Keywords: Dollarization, Financial Dollarization, Currency Substitution, Ratchet effect, Jordan, Monetary Policy, Ratchet Effect. JEL Classificatons: E44, F3, G17